(untitled) (CIPEEX, 2025)
In the contemporary scenario, health education plays a fundamental role in promoting the physical, emotional and social well-being of children and adolescents. The subject of sexual health and the prevention of sexually transmitted diseases (STIs) has emerged as an area that requires early attention and a didactic approach, mainly because the provision of sexual and reproductive health care is a right guaranteed by the Statute of the Child and Adolescent (ECA). From this perspective, it is of great practical and social relevance to educate this group about sexual health, with the aim of empowering these individuals to lead healthy and conscious lives. Objectives: To report on the implementation of an extension project applied to basic education through active methodology on sex education, physiology and pathology of the reproductive organs. Experience report The project was conceived by a private higher education institution in Goiás by students from the 3rd period of the medicine course for primary and secondary schools in the state network, between 11 and 20 years old, with an average of 1600 students. The students were divided into 17 classes in the morning and 17 in the afternoon, with an average of 7 students per class. Playful materials such as posters, games and anatomical models of the male and female sex organs were used to discuss the following topics: the male and female reproductive system, the hormonal cycle and contraception, STIs, physiology and breast and cervical cancer. The workshops were monitored by university lecturers and teachers from the school itself, both in order to assess the relevance of the activity and to answer any questions the students might have. Reflection on the experience The educational experience on sexual and reproductive health for young people, aimed at preventing STIs and other complications, was a success. By adopting the diversification of teaching methodologies as the foundation of the approach, including lectures, fun activities and group discussions, promoting engagement and active learning, the reinforcement effect produced a much greater absorption of knowledge. Also noteworthy was the collaboration between the workshop lecturers, teachers from the medical course and teachers from the school, enriching the experience and broadening the understanding of health. In addition, the emphasis on prevention of STIs, breast and cervical cancer enabled young people to take care of their health from an early age, especially at a stage when many are beginning their sexual lives. In this way, through a project that used various resources and promoted an open environment for questions and discussions, the objective was achieved through a didactic, inclusive and holistic approach.Conclusion:The report describes a model of health education that emphasizes multidimensional participation, integrating various actors, in order to build a more informed, healthier generation and, in addition, also contribute to building a more egalitarian and supportive society, where access to information and healthcare is universally guaranteed.